INFORME FINAL CALIDAD DE VIDA 2007 - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2010)
<!--[if gte mso 9]> Invitado 12.00 <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Abstract. In 2001, the Department of Metropolitan Planning of the city of Medellín realized the Survey of Quality of Vida (ECV), which collected data on the conditions of life of the inhabitants of the city. These indicators allowed obtaining measurements on the conditions of life for the homes in each commune of the urban area, and the five "corregimientos" of the rural area. From the 2001´s, it has been continued realizing the ECV annually with the purpose of to investigate the evolution of the conditions of life of the homes of the city with respect to the found ones in the basic information of year 2001. The objective of this document is to present the update of the measurements of conditions of life in Medellín based on the Survey of Quality of Life for year 2007 and for presenting its evolution from the 2001. Resumen. En el año 2001, el Departamento de Planeación Metropolitana de la ciudad de Medellín realizó La Encuesta de Calidad de Vida (ECV), la cual recogió información relevante sobre las condiciones de vida de los habitantes de la ciudad. En el 2002, Castaño et al., construyeron un indicador urbano y uno rural para medir las condiciones de vida en la ciudad teniendo como base la información proporcionada por dicha encuesta. Estos indicadores permitieron obtener mediciones sobre las condiciones de vida para los hogares en cada comuna del área urbana, y cada corregimiento del área rural. A partir del año 2004, Planeación Metropolitana ha seguido realizando anualmente la ECV con el fin de investigar la evolución de las condiciones de vida de los hogares de la ciudad con respecto a las halladas en la información de base del año 2001.